2018
DOI: 10.1108/imr-09-2013-0207
|View full text |Cite
|
Sign up to set email alerts
|

From outsider to insider: how creative professional service firms internationalise

Abstract: Purpose-The management of reputation and status is central to creative professional service firms (CPSFs) rendering the internationalisation process a particular challenge. We build on arguments that internationalisation requires moving from outsidership to insidership within client networks and focus on how CPSFs build signals about quality to start this process. Design/methodology/approach-The exploration draws from the international business, professional services and organizational status bodies of literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 75 publications
4
14
0
Order By: Relevance
“…The lack of connections assumed as a result of low presence in the markets and low levels of communication, what is in the literature highlighted as a crucial dimension to develop strong partnerships (Musteen et al, 2010). These results also meet the previous knowledge about the need to signal building for reputation and status in international business and to strengthen networks (McQuillan et al, 2018). In brief, the study shows that higher-status countries such as Germany pay less attention to the possibility of partnerships with low-reputation countries in the case of international business partnerships in the consulting sector.…”
Section: Discussion and Management Recommendationssupporting
confidence: 79%
See 3 more Smart Citations
“…The lack of connections assumed as a result of low presence in the markets and low levels of communication, what is in the literature highlighted as a crucial dimension to develop strong partnerships (Musteen et al, 2010). These results also meet the previous knowledge about the need to signal building for reputation and status in international business and to strengthen networks (McQuillan et al, 2018). In brief, the study shows that higher-status countries such as Germany pay less attention to the possibility of partnerships with low-reputation countries in the case of international business partnerships in the consulting sector.…”
Section: Discussion and Management Recommendationssupporting
confidence: 79%
“…To help companies in their internationalisation process, professional consultancy firms have advantages in collaborating with international consultancy services to build better networks, reduce costs and access specific knowledge of markets. The literature has highlighted the importance of partnerships among professional consultancy firms (Greenwood and Empson, 2003;Empson and Chapman, 2006;Empson et al, 2013), but little is known about partnerships between consultancy firms in the context of internationalisation, besides the importance of signal building of status and reputation for the establishment of international networks (McQuillan et al, 2018).…”
Section: International Business Consultancy Firms 315mentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary literature theorizing firm internationalization, however, also stresses the importance of network insidership (Johanson and Vahlne, 2011) and knowledge sharing, joint innovation and information gathering with network partners (Chetty and Stangl, 2010;Felzensztein et al, 2015;Hilmersson and Jansson, 2012;Johanson and Vahlne, 2009;Odlin and Benson-Rea, 2017;Paul et al, 2017). Although recent research has suggested that small KIS firms, in particular, leverage strong local embeddedness through client, industry and institutional networks to internationalize (McQuillan et al, 2018), our understanding of the role of the firm's network attributes for entry mode choice remains limited (Sedziniauskiene et al, 2019).…”
Section: Introductionmentioning
confidence: 99%